The Use of Interactive Media to Improve Student Engagement in Primary Schools - Kesuma, Siti Khovifah (International Conference on Elementary Education, 2025)
The use of technology has become inevitable in the fast-growing digital age. Advances in information and communication technology have changed almost every aspect of life. One area affected is education. This study examines how interactive media tools can help students become more engaged in elementary school. This research aims to improve understanding of interactive media and analyze various literature studies that show that technology can aid education, make lessons more interesting and entertaining, and support different learning styles. This research explores issues related to interactive media in the classroom. This is done through a qualitative approach. The results of the study show that interactive media not only increase students' engagement, but also improve their experience, help better master educational material, and create an interesting learning environment. This study also suggests that teachers use interactive learning tools to increase students' learning potential in primary schools. Additionally, this study provides recommendations for future researchers regarding nutritional supplements aimed at increasing student engagement.